Photosynthetic responses of lettuce to downy mildew infection and cytokinin treatment - Prokopová, Jitka; Spundová, Martina; Sedlárová, Michaela; Husicková, Alexandra; Novotný, Radko; Dolezal, Karel; Naus, Jan; Lebeda, Ales (Plant physiology and biochemistry, 2010)
Changes in primary metabolism of lettuce, Lactuca sativa L. (cv. Cobham Green), induced by compatible interaction with the biotrophic oomycete pathogen Bremia lactucae Regel (race BL 16), under two intensities of illumination in the presence and absence of exogenous cytokinins were studied by chlorophyll fluorescence imaging. Thirteen days post-inoculation leaf discs infected by B. lactucae exhibited impairments of photosynthesis associated with biotrophic infections, including: reductions in photosynthetic pigment contents and the maximum quantum yield of photosystem II photochemistry (F(V)/F(M)), inhibition of electron transport (Phi(PSII)) and increased non-photochemical chlorophyll fluorescence quenching (NPQ). Detected changes in photosynthetic parameters correlated with the leaf area colonized by the pathogen's intercellular hyphae. Applications of two cytokinins, benzylaminopurine and meta-topolin, previously shown to suppress B. lactucae sporulation if applied 24 h prior to inoculation at a concentration of 200 microM, retarded the pathogen's asexual reproduction with no apparent negative effects on the host's photosynthetic apparatus. However, long-lasting treatment of healthy tissues with this high concentration of exogenous cytokinin led to effects parallel to pathogenesis: reductions in photosynthetic pigment contents accompanied by inhibition of photosystem II photochemistry and electron transport. These effects of both prolonged exposure to cytokinins and the pathogenesis were weaker in discs exposed to the lower photosynthetic photon flux density. The role of cytokinins in plant-biotrophic pathogen interactions and their potential as disease control agents are discussed.
Keywords: Lactuca; Cytokinins; cytokininy; chlorofyl; fotosystém II (proteinový komplex); Oomycetes; Fluorescence; Photosystem II Protein Complex; Plant Leaves; regulátory růstu rostlin; chloroplasty; transmisní elektronová mikroskopie; fluorescence; fotosyntéza; Host-Pathogen Interactions; salát (hlávkový); oomycety; Benzyl Compounds; Photosynthesis; interakce hostitele a patogenu; Microscopy, Electron, Transmission; Chlorophyll; nemoci rostlin; Purines; puriny; benzylové sloučeniny; Plant Growth Regulators; listy rostlin; Plant Diseases; Chloroplasts